The Concurrent Objects Calculus - Zhang Qian; Li Weihua; Chen Shihong (Technology of Object Oriented Languages and Systems. 27th, 1998)
Research in concurrent object-oriented programming languages has suffered from the lack of a widely accepted formal foundation for describing the semantics of concurrent object systems. Based on the /spl pi/-calculus and the actor model respectively, people have tried to define a common semantic framework for concurrent object-oriented programming. In this paper, we try to compromise these two approaches. We define a formalism that enjoys a clean formal definition which allows the reuse of standard results of the theory of concurrency while preserving a high-level object-oriented programming style. We propose an actor algebra and a concurrent object calculus, and then we give the translation relationship between the two.